Perception of organ donation and its basic norms: A study among hospital employees - Ghosh, Anasuya; Ben, Riya; Venkata Nikesh Kumar Mallampati; Subhramoy Chaudhury; Mondal, Astom (Asian Journal of Medical Sciences, 2025)
Background: Organ donation is a process of retrieving an organ or tissue from a living or deceased doner and transplanting it to a recipient to save his life. Every year lakhs of patients are diagnosed with organ failure in this country; however, only 2–3% requirement is met and large number of patients die because lack of donated organs. Lack of awareness and motivation toward organ donation seems to be the major reason for the lack of supply of donated organ. Aims and Objectives: The present study was planned to assess the awareness and motivation toward organ donation among the support employees of a tertiary care medical organization. Materials and Methods: The study was conducted on 150 non-medical employees at a newly established teaching hospital at West Bengal. All the participants were individually approached for a face-to-face interview using a pre-structured and pre-validated questionnaire. The data were analyzed using Microsoft excel and Stata 12 software. Results: Among the study participants, 84.66% were aware about organ donation but only 36.66% expressed willingness for organ donation. The willingness was higher among male. The knowledge about organ donation was inadequate (mean knowledge score <50%). There was strong positive co-relation between mean knowledge score and mean motivation score. Conclusion: The non-medical employees have inadequate knowledge regarding the facts and legislation of organ donation. Targeted and focused sessions about organ donation should be arranged for them to address the knowledge-gap.